Estudio de prefactibilidad para la implementación de una planta de producción de leche vegetal dirigida al consumo de Lima Metropolitana - Abusabal Viale, Jean Pierre (2018)
The main objective of this project was the implementation of an organic vegetable milk production facility. It was fundamental to follow a methodology that evaluated its market, technical and financial viability.